Algerian Efl Students’ Perspectives And Practices On Ai-enabled Learning At The University Of Medea - Oussama Boukhelkhal (The Journal of Studies in Language, Culture and Society, 2025)
This exploratory research investigates Algerian university students' perspectives and practices toward AI-enabled learning and redraws relevant pedagogical conclusions. With this aim in mind, a self-designed questionnaire was administered to a sample of 205 EFL students enrolled in both undergraduate and master’s programs at the Foreign Languages Department (English Section), Medea University, Algeria. The quantitative results revealed that the majority of EFL students had already integrated AI-powered instruments into their learning, particularly ChatGPT, which was the most widely used. The subjects primarily employed AI for writing, grammar, and vocabulary development, with less emphasis on speaking and listening skills. The analysis also showed that students displayed significantly positive viewpoints toward AI-assisted EFL learning because it offered a streamlined learning process, immediate feedback, target language development, and personalized learning. However, students identified several drawbacks, namely excessive reliance on AI, negative impact on their critical thinking, and the problem of unreliable AI-generated data. They also faced some challenges, such as limited access to advanced AI tools, privacy and security issues, and a lack of guidance on how to use AI thoughtfully and responsibly. The findings may lead policymakers and educators to address the often-problematic relationship between AI-based systems and the EFL learning/teaching practice at the University of Medea in Algeria and other similar higher education institutions, wherein a comprehensive framework for AI-enabled education, at this juncture at least, remains enveloped in a veil of uncertainty.